Chronobiologic perspectives of black time—Accident risk is greatest at night: An opinion paper*. (August 2015) - Reinberg, Alain; Smolensky, Michael H.; Riedel, Marc; Touitou, Yvan; Floc'h, Nadine Le; Clarisse, René; Marlot, Michel; Berrez, Stéphane; Pelisse, Didier; Mauvieux, Benoît
<x xml:space="preserve">Abstract</x> Simon Folkard in 1997 introduced the phrase black time to draw attention to the fact that the risk of driving accidents (DA) is greater during the night than day in usually diurnally active persons. The 24 h temporal pattern in DA entails circadian rhythms of fatigue and sleep propensity, cognitive and physical performance, and behavior that are controlled, at least in part, by endogenous clocks. This opinion paper extends the concept of black time to reports of excess nighttime accidents and injuries of workers and nocturnal occurrence of certain man-caused catastrophes. We explore the chronobiology of work-related black time accidents and injuries taking into account laboratory and field investigations describing, respectively, circadian rhythms in cognitive performance and errors and mistakes by employees in the conduct of routine occupational tasks. Additionally, we present results of studies pertaining to 24 h patterns of both the number and relative risk (number of events per h/number of workers exposed per h) of work-related accidents (WRA) and injuries (WRI) as well as indices of performance and alertness of a self-selected homogenous survivor cohort of French firefighters (FFs) to explore two possible explanations of black time, namely, 24 h variation in sleep propensity/drossiness characterized by a nocturnal peak and circadian rhythms in cognitive performance characterized by a nocturnal trough. We propose the 24 h pattern of WRA and WRI, particularly of FFs and other highly skilled self-selected cohorts, is more strongly linked to circadian rhythms of fatigue and sleepiness than cognitive performance. Other possible explanations –suppressed expression of circadian rhythms and/or unmasking of ultradian periodicities in cognitive performance in specific circumstances, e.g., highly stressful work, competitive, or life-threatening settings, are also discussed.